Cuproptosis-related risk score predicts prognosis and characterizes the tumor microenvironment in colon adenocarcinoma - Wang, Jinyan; Tao, Zhonghua; Wang, Biyun; Xie, Yizhao; Wang, Ye; Li, Bin; Cao, Jianing; Qiao, Xiaosu; Qin, Dongmei; Zhong, Shanliang; Hu, Xichun (Frontiers in Oncology, 2023)
Cuproptosis is a novel copper-dependent regulatory cell death (RCD), which is closely related to the occurrence and development of multiple cancers. However, the potential role of cuproptosis-related genes (CRGs) in the tumor microenvironment (TME) of colon adenocarcinoma (COAD) remains unclear. Our study systematically evaluated the characteristics of CRGs in COAD patients from genetic and transcriptional fields. We identified three molecular subtypes of cuproptosis based on CRGs expression profiles, and found that changes in multilayer CRGs were closely related to the clinical characteristics, overall survival (OS), different signaling pathways, and immune cell infiltration of TME. Differentially expressed genes (DEGs) from different molecular subtypes were analyzed by univariate Cox regression analysis to study their prognostic value. Patients were again divided into three gene subtypes, which were significantly correlated with CRGs expression, clinical characteristics (age, sex, grade, T and N stage) and prognosis, respectively, according to prognostic DEGs expression profile. The CRG Risk scoring system for survival prediction was further established and verified. Finally, a highly accurate nomogram was constructed to promote the clinical application of the CRG Risk scoring system. High CRG risk scores, characterized by high microsatellite instability (MSI-H), tumor mutation burden (TMB), and cancer stem cell (CSC) indices, as well as high stromal and immune scores in TME, predicted poor survival. In addition, CRG risk scores were closely associated with drug susceptibility. Our comprehensive analysis showed that CRGs were greatly associated with TME, clinicopathological characteristics, and prognosis of patient with COAD. These findings may promote our understanding of CRGs in COAD, providing new insights for physicians to predict prognosis and develop more precise and individualized therapy strategies.